Decomposing parasite fitness reveals the basis of specialization in a two‐host, two‐parasite system. Issue 4 (11th July 2018) - Lievens, Eva J. P.; Perreau, Julie; Agnew, Philip; Michalakis, Yannis; Lenormand, Thomas
Abstract: The ecological specialization of parasites–whether they can obtain high fitness on very few or very many different host species–is a determining feature of their ecology. In order to properly assess specialization, it is imperative to measure parasite fitness across host species; to understand its origins, fitness must be decomposed into the underlying traits. Despite the omnipresence of parasites with multiple hosts, very few studies assess and decompose their specialization in this way. To bridge this gap, we quantified the infectivity, virulence, and transmission rate of two parasites, the horizontally transmitted microsporidians Anostracospora rigaudi and Enterocytospora artemiae, in their natural hosts, the brine shrimp Artemia parthenogenetica and Artemia franciscana . Our results demonstrate that each parasite performs well on one of the two host species ( A. rigaudi on A. parthenogenetica, and E. artemiae on A. franciscana ), and poorly on the other. This partial specialization is driven by high infectivity and transmission rates in the preferred host, and is associated with maladaptive virulence and large costs of resistance in the other. Our study represents a rare empirical contribution to the study of parasite evolution in multihost systems, highlighting the negative effects of under‐ and overexploitation when adapting to multiple hosts.